Clinical observation of Сhronic granulomatous disease in a 6-year-old child - G. A. Kharchenko; O. G. Kimirilova (Детские инфекции (Москва))
Chronic granulomatous disease (CGD) is a hereditary disease caused by a genetic defect of violations of oxygen — dependent mechanisms of phagocytosis. Clinical manifestations of the disease are recurrent bacterial or fungal infections of the skin, hepatic abscesses, pneumonia, osteomyelitis, sepsis, meningitis et al. Most available laboratory method for the diagnosis of CGD is the test of histochemical nitro blue tetrazolium recovery (NBT-test). Allogeneic hematopoietic stem cell transplantation is considered a radical treatment for chronic granulomatous disease. The article presents a clinical observation of the manifestation of chronic granulomatous disease with an unfavorable outcome in a child aged 6 years.